Plant-soil interactions in succession on post-mining sites - Mudrák, Ondřej (Jihočeská univerzita, 2012)
Field observation and manipulative experiments were carried out to describe and test important processes affecting the plant succession on Sokolov post-mining sites. Examined was mainly effect of dominant tree species (which are planted or spontaneously established) on understory plants, litter decomposability and effect of earthworms (Lumbricidae) on late successional plant species.
Plant-soil interactions in succession on post-mining sites
Keywords: Post-mining sites; Restoration; Succession; Earthworms; Understory; Allelopathy; Decomposability; Plant litter; Post-mining sites; Restoration; Succession; Earthworms; Understory; Allelopathy; Decomposability; Plant litter